2016
DOI: 10.1111/bjd.14494
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epidermal stem cell markers in skin and adnexal malignancies

Abstract: Expression of potential stem cell markers of the epidermis and hair follicles was observed in skin tumours of appendages and BCCs. However, during tumour progression, many of these markers seemed to be downregulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
(117 reference statements)
0
13
0
Order By: Relevance
“…In addition to hair‐loss disorders, the SHG and bulge are of particular clinical relevance because they may give rise to at least some basal cell carcinoma (BCC) in human skin, and dysregulated Wnt signalling has also been implicated in BCC pathobiology . Clinically, this renders a systematic examination of Wnt signalling in these key epithelial progenitor cell compartments of human HFs important also from an oncological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hair‐loss disorders, the SHG and bulge are of particular clinical relevance because they may give rise to at least some basal cell carcinoma (BCC) in human skin, and dysregulated Wnt signalling has also been implicated in BCC pathobiology . Clinically, this renders a systematic examination of Wnt signalling in these key epithelial progenitor cell compartments of human HFs important also from an oncological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, investigating the neuronal and neuroendocrine regulation of SGs promises to contribute further to fields of broad biological interest, such as maintenance of stem cell niches (Liao & Nguyen, ; Füllgrabe et al ., ; Kretzschmar et al ., ), tumour development and progression (Kyllo, Brady & Hurst, ; Quist et al ., ), lipid synthesis (Guy, Ridden & Kealey, ; Schneider & Paus, ; Jester, Potma & Brown, ), autophagy (Fischer et al ., ; Rossiter et al ., ), and interaction of the nervous system with cardinal signalling pathways in peripheral tissues, i.e. Hedgehog (Allen et al ., ; Brownell et al ., ), Wingless (Kretzschmar et al ., ; Lim et al ., ), and Hippo pathway signalling (Yosefzon et al ., ).…”
Section: Major Open Questions and Translational Relevance Of Neuro‐rementioning
confidence: 99%
“…28 A study by Quist et al showed that expression of potential stem cell markers of the epidermis and HF was observed in the skin tumors of appendages and human basal cell carcinomas. 29 Also, they demonstrated that many of these markers appeared to be downregulated during tumor progression. These studies have expressed the importance of general HF markers in that it can change expression levels in some pathological conditions.…”
Section: Discussionmentioning
confidence: 99%